Combating Hoaxes in Elections: The Role of High School Education in Safeguarding Democracy - Hildawati; Pratiwi, Angelika Yuni; Two, Abril Tika Gagas; Julisa, Monika; Firmansyah, Yoki (Indonesian Journal of Education and Social Sciences, 2025)
The proliferation of hoaxes in Indonesia, particularly during election periods, poses significant challenges to the nation's democratic process by influencing public perception, destabilizing socio-political conditions, and undermining trust in institutions. This study explores the understanding and involvement of high school students in detecting hoaxes and monitoring information. Conducted at SMA Taruna Bumi Khatulistiwa Pontianak, the research utilized a qualitative descriptive method, involving 115 students who participated in the program "Detecting Hoaxes and Engaging in Participatory Monitoring." Data collection employed triangulation techniques, including interviews, observations, and documentation.The findings revealed that while most students are familiar with the concept of hoaxes and their basic forms, such as false news and manipulated images, their understanding of the broader socio-political and digital security impacts remains limited. Additionally, their participation in information monitoring is minimal, influenced by a lack of knowledge, skills, and motivation. The study identified key shortcomings in the current socialization program, including limited practical training, lack of interactive and participatory approaches, and inadequate emphasis on the long-term consequences of hoaxes. The research recommends enhancing the program through interactive activities, such as case simulations, digital literacy workshops, and collaborative anti-hoax campaigns. By equipping students with critical thinking and digital verification skills, and fostering collective awareness, the program can empower students to act as active agents in combating hoaxes and maintaining information integrity. This study underscores the importance of education and participatory approaches in addressing the challenges posed by hoaxes in the digital era.